Method for improving wear resistance of polytetrafluoroethylene and crosslinked polytetrafluoroethylene

By performing two proton beam irradiation treatments on the sintered polytetrafluoroethylene block, the problem of insufficient wear resistance of polytetrafluoroethylene is solved, and the high degree of cross-linking and uniform distribution of cross-linked polytetrafluoroethylene is achieved, which significantly improves its wear resistance.

CN119552404AActive Publication Date: 2025-03-04PEKING UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202311126194.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-01
Publication Date
2025-03-04
Estimated Expiration
2043-09-01

AI Technical Summary

Technical Problem

Polytetrafluoroethylene has poor radiation resistance and wear resistance, which limits its application in high-strength impact and friction environments.

Method used

The sintered PTFE block was subjected to two proton beam irradiation treatments, cooling after the first irradiation treatment, and then a second irradiation treatment, and finally cooling to obtain crosslinked PTFE.

Benefits of technology

The crosslinking degree and distribution uniformity of polytetrafluoroethylene are improved, and its wear resistance is significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119552404A_ABST
    Figure CN119552404A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of polymer modification, and provides a method for improving wear resistance of polytetrafluoroethylene and crosslinked polytetrafluoroethylene. The method comprises the following steps: (1) providing a polytetrafluoroethylene sintered block; (2) performing first irradiation treatment on the polytetrafluoroethylene sintered block by using a first proton beam; (3) performing second irradiation treatment on the material obtained in the step (2) by using a second proton beam; and (4) cooling the material obtained in the step (3) to obtain the crosslinked polytetrafluoroethylene. The first irradiation treatment and the second irradiation treatment are performed on the polytetrafluoroethylene sintered block, so that the obtained cross-linked polytetrafluoroethylene is relatively high in cross-linking degree and uniform in distribution, and the cross-linked polytetrafluoroethylene shows relatively excellent wear resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of polymer modification, and in particular relates to a method for improving the wear resistance of polytetrafluoroethylene and cross-linked polytetrafluoroethylene. Background Art

[0002] Polytetrafluoroethylene is an excellent engineering plastic with excellent chemical stability, extremely low friction coefficient and good thermal stability. It is known as the "king of plastics" and has been widely used in many fields. However, polytetrafluoroethylene has poor radiation resistance and wear resistance, which limits its application in strong radiation fields such as outer space and nuclear reactors. This requires modification of polytetrafluoroethylene, such as cross-linking modification of polytetrafluoroethylene, so that it can better adapt to the mechanical operating environment of high-intensity impact and friction. The cross-linking modification of polytetrafluoroethylene usually includes cross-linking polytetrafluoroethylene to reduce its crystallinity, but the traditional method results in a low degree of cross-linking of the cross-linked polytetrafluoroethylene, which has limited improvement in the wear resistance of polytetrafluoroethylene.

[0003] Therefore, the method for improving the wear resistance of polytetrafluoroethylene still needs to be improved. Summary of the invention

[0004] The present invention aims to solve one of the technical problems in the related art at least to a certain extent.

[0005] In a first aspect of the present invention, the present invention provides a method for improving the wear resistance of polytetrafluoroethylene, comprising the following steps:

[0006] (1) Providing polytetrafluoroethylene sintered blocks;

[0007] (2) performing a first irradiation treatment on the polytetrafluoroethylene sintered block using a first proton beam;

[0008] (3) performing a second irradiation treatment on the material obtained in step (2) using a second proton beam;

[0009] (4) Cooling the material obtained in step (3) to obtain cross-linked polytetrafluoroethylene.

[0010] The method provided by the present invention performs two irradiation treatments on a polytetrafluoroethylene sintered block, so that the obtained cross-linked polytetrafluoroethylene has a higher cross-linking degree and is evenly distributed, thereby making the cross-linked polytetrafluoroethylene exhibit better wear resistance.

[0011] According to an embodiment of the present invention, the energy E1 of the first proton beam is 0.3-1.5 MeV, and the dose F1 of the first proton beam is 0.1×10 14 -9.5×10 14 ion / cm 2The energy E2 of the second proton beam is 0.3-1.5 MeV, and the dose F2 of the second proton beam is 0.1×10 14 -9.5×10 14 ion / cm 2 ; wherein E1≠E2. Thus, by controlling the energy of the first proton beam and the second proton beam to be within the aforementioned range, the polytetrafluoroethylene sintered block can be effectively cross-linked, while reducing the possibility of carbonization of the polytetrafluoroethylene surface.

[0012] According to an embodiment of the present invention, the energy E1 of the first proton beam is 0.85-1.5 MeV, and the dose F1 of the first proton beam is 1×10 14 -9×10 14 ion / cm 2 .

[0013] According to an embodiment of the present invention, the energy E2 of the second proton beam is 0.3-0.8 MeV, and the dose F2 of the second proton beam is 1×10 14 -9×10 14 ion / cm 2 .

[0014] According to an embodiment of the present invention, the first irradiation treatment is carried out in a vacuum degree not higher than 1×10 -4 Pa conditions.

[0015] According to an embodiment of the present invention, the temperature of the first irradiation treatment is 325-360°C.

[0016] According to an embodiment of the present invention, the second irradiation treatment is carried out in a vacuum degree not higher than 1×10 -4 Pa conditions.

[0017] According to an embodiment of the present invention, the temperature of the second irradiation treatment is 325-360°C.

[0018] According to an embodiment of the present invention, step (1) includes: (1-1) cold pressing polytetrafluoroethylene powder to obtain a cold pressed product; (1-2) sintering the cold pressed product to obtain a polytetrafluoroethylene sintered block.

[0019] According to an embodiment of the present invention, the cold pressing conditions include: a pressure of 25-35 MPa; and / or a holding time of 0.5-2 min.

[0020] According to an embodiment of the present invention, the sintering includes: heating the cold pressed product to 150-250°C at a heating rate of 2-6°C / min and keeping the temperature for 1-3h, and then heating the product to 360-380°C at a heating rate of 2-6°C / min and keeping the temperature for 1-3h. The two-stage sintering process can reduce the risk of cracks on the surface of the polytetrafluoroethylene sintered block, thereby improving the yield of the polytetrafluoroethylene sintered block.

[0021] In the second aspect of the present invention, the present invention provides cross-linked polytetrafluoroethylene prepared by the above method. The cross-linked polytetrafluoroethylene obtained by the method of the present invention has a high degree of cross-linking and uniform distribution, and exhibits excellent wear resistance. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:

[0023] Figure 1 It is a Srim program simulation diagram of the relationship between the injection depth and energy after the proton beam irradiated the polytetrafluoroethylene sintered block in Comparative Example 1 and Comparative Example 2;

[0024] Figure 2 is an infrared spectra of the cross-linked polytetrafluoroethylene of Example 1, Comparative Example 1 and Comparative Example 3;

[0025] Figure 3 1 is the X-ray diffraction pattern of the cross-linked polytetrafluoroethylene of Example 1, Comparative Example 1 and Comparative Example 3. DETAILED DESCRIPTION

[0026] The embodiments of the present invention are described in detail below. The embodiments described below are exemplary and are only used to explain the present invention, and should not be construed as limiting the present invention.

[0027] Irradiation modification is a method for modifying polytetrafluoroethylene materials. During the irradiation process, polytetrafluoroethylene (PTFE) undergoes a cross-linking reaction, and the molecular structure changes from a highly linear structure to a network structure. However, when irradiating with a proton beam of a single energy and dose, the chemical reaction induced by the irradiation is incomplete and insufficient, resulting in a low degree of cross-linking on the surface of the cross-linked polytetrafluoroethylene sample, and limited improvement in the wear resistance of polytetrafluoroethylene.

[0028] To this end, a first aspect of the present invention provides a method for improving the wear resistance of polytetrafluoroethylene, comprising the following steps:

[0029] (1) Providing polytetrafluoroethylene sintered blocks;

[0030] (2) performing a first irradiation treatment on the polytetrafluoroethylene sintered block using a first proton beam;

[0031] (3) performing a second irradiation treatment on the material obtained in step (2) using a second proton beam;

[0032] (4) Cooling the material obtained in step (3) to obtain cross-linked polytetrafluoroethylene.

[0033] The method provided by the present invention is to perform a first irradiation treatment and a second irradiation treatment on a polytetrafluoroethylene sintered block, wherein the first irradiation and the second irradiation treatment can cause the molecular chains of the polytetrafluoroethylene sintered block to break and crosslink, and the crosslinking reaction caused by the two irradiations is more sufficient, and the obtained crosslinked polytetrafluoroethylene has a high degree of crosslinking and is evenly distributed, thereby making the crosslinked polytetrafluoroethylene show better wear resistance. Specifically, when the polytetrafluoroethylene sintered block is irradiated by a high-energy proton beam, the CF bond breaks, free radicals and free fluorine atoms are generated, the main chain carbon that loses the protection of the fluorine atom is exposed to the irradiation, the CC bond breaks to generate chain end free radicals, these free radicals collide with each other and combine, so that the molecular structure of the polytetrafluoroethylene changes from a highly linear state to an H-type or T-type, and the crosslinking reaction between the free radicals is random and disordered, so that the obtained crosslinked polytetrafluoroethylene presents an irregular network structure. The present invention uses a proton beam to perform two irradiation treatment operations on the polytetrafluoroethylene sintered block, the first irradiation treatment preliminarily realizes intermolecular crosslinking, and the second irradiation treatment can perfect the intermolecular crosslinking. In this way, the crosslinking caused by the two irradiations is superimposed on each other, making the formed crosslinking system more uniform and complete, and obtaining crosslinked polytetrafluoroethylene with a high degree of intermolecular crosslinking and uniformity. Since the attraction between the molecules of the crosslinked polytetrafluoroethylene is strong, it is difficult to carry away the molecules of the crosslinked polytetrafluoroethylene under the friction of the external load, thereby making the crosslinked polytetrafluoroethylene show higher wear resistance.

[0034] In some embodiments, the process of irradiating the polytetrafluoroethylene sintered block with the first proton beam and the second proton beam may be performed in an electrostatic accelerator.

[0035] According to the present invention, the energy E1 of the first proton beam may be 0.3-1.5 MeV, for example, the energy is 0.3 MeV, 0.5 MeV, 0.8 MeV, 0.85 MeV, 1 MeV, 1.2 MeV, 1.3 MeV, 1.5 MeV, etc., and the dose F1 of the first proton beam may be 0.1×10 14 -9.5×10 14 ion / cm 2 For example, the dose is 0.1×10 14 ion / cm 2 , 1×10 14 ion / cm 2 , 5×10 14 ion / cm 2 ,7×10 14 ion / cm2 , 8×10 14 ion / cm 2 , 9.5×10 14 ion / cm 2 The energy E2 of the second proton beam may be 0.3-1.5 MeV, for example, the energy is 0.3 MeV, 0.5 MeV, 0.8 MeV, 0.85 MeV, 1 MeV, 1.2 MeV, 1.3 MeV, 1.5 MeV, etc., and the dose F2 of the second proton beam may be 0.1×10 14 -9.5×10 14 ion / cm 2 For example, the dose is 0.1×10 14 ion / cm 2 , 1×10 14 ion / cm 2 , 5×10 14 ion / cm 2 ,7×10 14 ion / cm 2 , 8×10 14 ion / cm 2 , 9.5×10 14 ion / cm 2 ; Wherein, E1≠E2. By controlling the energy and dose of the first proton beam and the second proton beam to meet the aforementioned range, and the energies of the first proton beam and the second proton beam are different, effective cross-linking occurs between the molecules of the polytetrafluoroethylene sintered block during the irradiation process, while trying to avoid excessive energy and dose to carbonize the surface of polytetrafluoroethylene.

[0036] According to the present invention, the implantation depths of the first proton beam and the second proton beam can be independently 4-23 μm, which can further reduce the risk of the polytetrafluoroethylene sintered block being broken down.

[0037] In some specific embodiments, the energy of the first proton beam is 0.85-1.5 MeV, and the dose is 1×10 14 -9×10 14 ion / cm 2 .

[0038] In some specific embodiments, the implantation depth of the first proton beam is 13-23 μm.

[0039] In some specific embodiments, the energy of the second proton beam is 0.3-0.8 MeV, and the dose is 1×10 14 -9×10 14 ion / cm 2 .

[0040] In some specific embodiments, the implantation depth of the second proton beam is 4-10 μm.

[0041] In some embodiments, the temperatures of the first irradiation treatment and the second irradiation treatment are independently 325-360° C., for example, 325° C., 338° C., 350° C., 360° C., etc. When the polytetrafluoroethylene sintered block is irradiated within this temperature range, the generated free radicals can collide and combine with each other more fully under the action of thermal motion, and cross-linking occurs, thereby obtaining cross-linked polytetrafluoroethylene with a high degree of cross-linking and uniform distribution.

[0042] In some embodiments, the first irradiation treatment and the second irradiation treatment are both performed under vacuum conditions to minimize energy loss or path deviation of the proton beam due to interference from atmospheric molecules. Optionally, the vacuum degree is not higher than 1×10 -4 Pa.

[0043] It can be understood that the operation process of the first irradiation treatment and the second irradiation treatment during the irradiation process can be performed continuously, that is, the second irradiation treatment is performed immediately after the first irradiation is completed.

[0044] According to the present invention, the polytetrafluoroethylene sintered block provided in step (1) can be obtained commercially or prepared, for example, by cold pressing and sintering polytetrafluoroethylene powder.

[0045] In some embodiments, step (1) may include:

[0046] (1-1) cold pressing polytetrafluoroethylene powder to obtain a cold pressed product;

[0047] (1-2) Sintering the cold pressed product to obtain a polytetrafluoroethylene sintered block.

[0048] In some embodiments, the polytetrafluoroethylene powder has a Dv50 of 12-18 μm.

[0049] In some embodiments, the cold pressing pressure is 25-35 MPa, such as 25 MPa, 30 MPa, 35 MPa, etc.; the cold pressing holding time is 0.5-2 min, such as 0.5 min, 1 min, 2 min. Under this condition, the polytetrafluoroethylene powder can be pressed into a shape to obtain a cold pressed product to meet the requirements of the sample shape in the subsequent sintering process.

[0050] In some embodiments, the sintering treatment includes: heating the cold pressed product to 150-250°C at a heating rate of 2-6°C / min and keeping it warm for 1-3h, for example, the heating rate can be 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, etc., the temperature can be 150°C, 200°C, 250°C, etc., and the holding time can be 1h, 2h, 3h, etc.; then heating to 360-380°C at a heating rate of 2-6°C / min and keeping it warm for 1-3h, for example, the heating rate can be 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, etc., the temperature can be 360°C, 370°C, 380°C, etc., and the holding time can be 1h, 2h, 3h, etc. After the holding is completed, it can be cooled naturally to room temperature. By adopting a two-stage sintering process and controlling the heating rate of the sintering process within the aforementioned range, patterns or cracks on the surface of the polytetrafluoroethylene sintered block can be reduced or even eliminated, thereby improving the yield of the polytetrafluoroethylene sintered block.

[0051] In the second aspect of the present invention, the present invention provides cross-linked polytetrafluoroethylene prepared by the above method. Using the method provided by the present invention, the cross-linked polytetrafluoroethylene prepared has a high degree of cross-linking between molecules and is evenly distributed, and the cross-linked polytetrafluoroethylene has high wear resistance.

[0052] In the present invention, during the proton beam irradiation of the polytetrafluoroethylene sintered block, the CF bonds in the polytetrafluoroethylene sintered block are broken, the active fluorine atoms react to generate fluorine-containing small molecular gases and escape, while the carbon atoms on the main chain remain in the cross-linked polytetrafluoroethylene, thereby reducing the relative proportion of F in the cross-linked polytetrafluoroethylene and increasing the relative proportion of C. Optionally, the ratio of the number of fluorine atoms to the number of carbon atoms in the cross-linked polytetrafluoroethylene is 0.59-1.14, which can be measured by X-ray photoelectron spectroscopy analysis.

[0053] The scheme of the present invention is described below by means of specific examples. It should be noted that the following examples are only used to illustrate the present invention and should not be regarded as limiting the scope of the present invention.

[0054] In the following examples and comparative examples, polytetrafluoroethylene powder was purchased from Shenzhen Xinyi Technology Co., Ltd. with a brand name of MP1000.

[0055] Cross-linked polytetrafluoroethylene was prepared using a 1.7MV tandem electrostatic accelerator equipped with a vacuum system and a heating system at the Nuclear Technology Application Laboratory of Peking University.

[0056] Example 1

[0057] (1) Preparation of polytetrafluoroethylene sintered blocks

[0058] 1.0 g of polytetrafluoroethylene powder was weighed and placed in a circular mold with a diameter of 1 cm. The polytetrafluoroethylene powder in the circular mold was pressurized to 30 MPa using a hydraulic press and maintained at this pressure for 1 min, then the pressure was released to obtain a cold-pressed product.

[0059] The cold pressed product was placed in an alumina ark and sintered in a muffle furnace. The temperature was first increased to 200°C at a heating rate of 3°C / min and kept at this temperature for 2 hours. The temperature was then increased to 380°C at a heating rate of 3°C / min and kept at this temperature for 2 hours. The product was then cooled to room temperature with the furnace to obtain a polytetrafluoroethylene sintered block.

[0060] (2) Preparation of cross-linked polytetrafluoroethylene

[0061] Turn on the vacuum system and heating system of the 1.7 MV tandem electrostatic accelerator and control the vacuum degree to 1×10 -4 Pa, the temperature is 338 ° C, and the polytetrafluoroethylene sintered block is irradiated with a proton beam using a proton accelerator. The polytetrafluoroethylene sintered block is first exposed to a proton beam with an energy of 1.0 MeV and a dose of 5 × 10 14 ion / cm 2 The first irradiation treatment was followed by a proton beam with an energy of 0.5 MeV and a dose of 5 × 10 14 ion / cm 2 The second irradiation treatment is performed, and then the heating system is turned off. The material obtained after the two irradiations is cooled to room temperature, and finally the vacuum system is turned off to obtain block-shaped cross-linked polytetrafluoroethylene, which is recorded as C1.

[0062] Example 2

[0063] The preparation of the polytetrafluoroethylene sintered block is the same as that in Example 1, except that in the preparation of the cross-linked polytetrafluoroethylene, the polytetrafluoroethylene sintered block is first subjected to a proton beam with an energy of 1.2 MeV and a dose of 5×10 14 ion / cm 2 The first irradiation treatment was followed by a proton beam with an energy of 0.5 MeV and a dose of 7 × 10 14 ion / cm 2 The cross-linked polytetrafluoroethylene sample prepared by the second irradiation treatment is recorded as C2.

[0064] Example 3

[0065] The preparation of the polytetrafluoroethylene sintered block is the same as that in Example 1, except that in the preparation process of the cross-linked polytetrafluoroethylene, the polytetrafluoroethylene sintered block is first subjected to a proton beam with an energy of 1.5 MeV and a dose of 5×10 14 ion / cm 2 The first irradiation treatment was followed by a proton beam with an energy of 0.3 MeV and a dose of 5 × 1014 ion / cm 2 The cross-linked polytetrafluoroethylene sample prepared by the second irradiation treatment is recorded as C3.

[0066] Comparative Example 1

[0067] The preparation of the polytetrafluoroethylene sintered block is the same as that in Example 1, except that in the preparation process of the cross-linked polytetrafluoroethylene, the polytetrafluoroethylene sintered block is only subjected to proton beam energy of 0.5 MeV and a dose of 5×10 14 ion / cm 2 The cross-linked polytetrafluoroethylene sample prepared by irradiation treatment is recorded as D1.

[0068] Comparative Example 2

[0069] The preparation of the polytetrafluoroethylene sintered block is the same as that in Example 1, except that in the preparation process of the cross-linked polytetrafluoroethylene, the polytetrafluoroethylene sintered block is only subjected to a proton beam with an energy of 1 MeV and a dose of 5×10 14 ion / cm 2 The cross-linked polytetrafluoroethylene sample prepared by irradiation treatment is recorded as D2.

[0070] Comparative Example 3

[0071] The polytetrafluoroethylene sintered block prepared in Example 1 was used as a comparative sample, and this sample was recorded as D3.

[0072] Test Case

[0073] 1. Density test

[0074] Density tests were performed on samples C1-C3 and D1-D3.

[0075] Test method: First measure the buoyancy of the sample immersed in water to obtain the volume of water displaced (i.e., sample volume), then measure the mass of the sample, and divide the mass of the sample by the sample volume to obtain the sample density.

[0076] 2. Wear resistance test

[0077] The samples C1-C3 and D1-D3 were subjected to wear resistance tests.

[0078] Test method: The sample to be tested is fixed on the stage of the wear test machine and rotated at a certain speed. A certain load is loaded on the mechanical grinding head, and the grinding head and the rotating sample are in contact with each other to generate friction. After the wear test time t of mutual friction, mass loss will occur in the friction area of ​​the tested sample. Δm represents the mass difference (i.e. friction loss mass) between the tested sample before and after the wear test, r represents the average radius of rotation, n represents the number of rotations per unit time, t represents the wear test time, F represents the load loaded on the grinding head, R is the radius of the grinding head, l is the average width of the wear mark, and the calculation formula for the wear depth h of the tested sample is as follows:

[0079]

[0080] During the test, the wear resistance test was carried out using a ball-on-disc friction loss testing machine in an atmospheric atmosphere and at room temperature. The loaded load F was 1N, the grinding head radius R was 3.0mm, the rotational motion radius r was 3.0mm, the rotation speed n was 300rpm, the wear resistance test time t was 15min, and the density ρ was the density of the sample in Table 1.

[0081] Table 1

[0082] Serial number Friction loss mass (g) Wear depth(μm) <![CDATA[Sample density (g / cm 3 )]]> Example 1 <![CDATA[1.00×10 -4 ]]> 8.20 2.201 Example 2 <![CDATA[0.84×10 -4 ]]> 7.90 2.204 Example 3 <![CDATA[0.71×10 -4 ]]> 7.48 2.198 Comparative Example 1 <![CDATA[4.00×10 -4 ]]> 20.60 2.199 Comparative Example 2 <![CDATA[2.50×10 -4 ]]> 18.30 2.201 Comparative Example 3 <![CDATA[7.00×10 -4 ]]> 29.90 2.201

[0083] As can be seen from the above table, the wear resistance of the cross-linked polytetrafluoroethylene obtained by two irradiations in Examples 1-3 is greatly improved compared with the polytetrafluoroethylene sintered block in Comparative Example 3 and the cross-linked polytetrafluoroethylene obtained by one irradiation in Comparative Example 1-2, which is reflected in the decrease of mass friction loss mass and wear depth. Therefore, the wear resistance of polytetrafluoroethylene can be effectively improved by the method provided by the present invention.

[0084] Figure 1 This is a simulation diagram of the relationship between the injection depth and energy of a proton beam irradiated polytetrafluoroethylene sintered block. The simulation uses the Srim program. From Figure a, it can be seen that the injection depth of a proton beam with an energy of 0.5MeV is 6μm, and the injection depth of a proton beam with an energy of 1.0MeV is 16μm. By comparison Figure 1 It can be seen from a and b in that when the proton beam irradiates the polytetrafluoroethylene sintered block, its energy loss is mainly electron energy loss, and the magnitude of nuclear energy loss is smaller than that of electron energy loss. Electron energy loss refers to the energy lost by the inelastic collision between the incident particles and the extranuclear electrons of the target atoms, which excites and ionizes the chemical bonds in the polytetrafluoroethylene sintered block, and then cross-links. The magnitude of electron energy loss is positively correlated with the cross-linking degree of cross-linked polytetrafluoroethylene, that is, the peak position of electron energy loss of the proton beam in the cross-linked polytetrafluoroethylene reflects the position where the proton beam induces the maximum cross-linking degree.

[0085] Figure 2The results of infrared spectroscopy testing of the chemical structures of Example 1 (irradiated sample 2), the cross-linked polytetrafluoroethylene of Comparative Example 1 (irradiated sample 1), and the polytetrafluoroethylene sintered block of Comparative Example 3 (original sample) are shown in FIG. -1 The absorption peak at 1211cm is caused by the stretching vibration of the CC bond of the PTFE main chain; -1 and 1154cm -1 The absorption peaks at 639cm are caused by the asymmetric stretching vibration and symmetric stretching vibration of the -CF2- unit. -1 、555cm -1 、516cm -1 The absorption peaks at 1730 cm-1 and 1740 cm-2 are caused by the out-of-plane rocking vibration, in-plane bending vibration and in-plane rocking vibration of -CF2-, respectively. It can be seen from the figure that the peak intensity of the cross-linked polytetrafluoroethylene obtained in Example 1 and Comparative Example 1 is lower than that of the polytetrafluoroethylene sintered block, and the peak intensity of the cross-linked polytetrafluoroethylene in Example 1 decreases more significantly. In addition, it can be observed from the figure that the cross-linked polytetrafluoroethylene obtained in Example 1 and Comparative Example 1 has a peak intensity of 1730 cm-1 and 1740 cm-1 respectively. -1 、983cm -1 、778cm -1 、730cm -1 and 720cm -1 A new absorption peak appeared at 1300-1400 cm -1 This indicates that a new chemical structure appears in the PTFE sintered block after irradiation. Among them, the cross-linked PTFE has an absorption band at 1730cm -1 The absorption peak at 983cm comes from the vibration of -CF=CF-; -1 The absorption peak at 778cm comes from the side chain -CF3; -1 The absorption peak at 730cm comes from the vibration of the molecular chain in the amorphous component of PTFE; -1 and 720cm -1 The double peak at 1300-1400cm is the characteristic peak of the in-plane swing vibration of -CH2-, which is split in the long-chain saturated crystalline compound; -1 The nearby absorption bands are caused by deformation vibrations of groups containing CH bonds.

[0086] Figure 3The results of crystallinity test on the cross-linked polytetrafluoroethylene of Example 1 (irradiated sample 2) and Comparative Example 1 (irradiated sample 1), and the polytetrafluoroethylene sintered block of Comparative Example 3 (original sample) using an X-ray diffractometer show that the wave packet intensity of the diffraction peak of the cross-linked polytetrafluoroethylene of Example 1 near 2θ=16° is greater than that of the cross-linked polytetrafluoroethylene of Comparative Example 1 near 2θ=16°, while no wave packet is observed at the diffraction peak of the polytetrafluoroethylene sintered block at 2θ=16°, which indicates that non-crystalline components exist in the cross-linked polytetrafluoroethylene. At the same time, both the polytetrafluoroethylene sintered block and the cross-linked polytetrafluoroethylene have diffraction peaks at 2θ=18° and 32°, but the diffraction peak intensity of the polytetrafluoroethylene sintered block is the strongest, the diffraction peak intensity of the cross-linked polytetrafluoroethylene of Comparative Example 1 is second, and the diffraction peak of the cross-linked polytetrafluoroethylene of Example 1 is the weakest. According to the Bragg equation, the X-ray diffraction angle remains unchanged and the peak position does not shift, which means that the polytetrafluoroethylene sintered block undergoes a cross-linking reaction under proton beam irradiation, the crystallinity of the obtained cross-linked polytetrafluoroethylene decreases, and the amorphous component increases.

[0087] In the description of this specification, the description with reference to the term "some embodiments" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment are included in at least one embodiment of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in a suitable manner in any one or more embodiments or examples. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of different embodiments or examples, unless they are contradictory. In addition, it should be noted that in this specification, the terms "first" and "second" are used for descriptive purposes only and cannot be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated.

[0088] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.

Claims

1. A method for improving the wear resistance of polytetrafluoroethylene, characterized in that: The following steps are involved: (1) Providing polytetrafluoroethylene sintered blocks; (2) performing a first irradiation treatment on the polytetrafluoroethylene sintered block using a first proton beam; (3) performing a second irradiation treatment on the material obtained in step (2) using a second proton beam; (4) Cooling the material obtained in step (3) to obtain cross-linked polytetrafluoroethylene.

2. The method according to claim 1, characterized in that The energy E1 of the first proton beam is 0.3-1.5 MeV, and the dose F1 of the first proton beam is 0.1×10 14 -9.5×10 14 ion / cm 2 ; The energy E2 of the second proton beam is 0.3-1.5 MeV, and the dose F2 of the second proton beam is 0.1×10 14 -9.5×10 14 ion / cm 2 ; Among them, E1≠E2.

3. The method according to claim 1, characterized in that The energy E1 of the first proton beam is 0.85-1.5 MeV, and the dose F1 of the first proton beam is 1×10 14 -9×10 14 ion / cm 2 .

4. The method according to claim 1, characterized in that: The energy E2 of the second proton beam is 0.3-0.8 MeV, and the dose F2 of the second proton beam is 1×10 14 -9×10 14 ion / cm 2 .

5. The method according to claim 1, characterized in that The first irradiation treatment satisfies at least one of the following conditions: The vacuum degree is not higher than 1×10 -4 Pa conditions; The temperature is 325-360℃.

6. The method according to claim 1, characterized in that The second irradiation treatment satisfies at least one of the following conditions: The vacuum degree is not higher than 1×10 -4 Pa conditions; The temperature is 325-360℃.

7. The method according to claim 1, characterized in that Step (1) comprises: (1-1) cold pressing polytetrafluoroethylene powder to obtain a cold pressed product; (1-2) Sintering the cold pressed product to obtain a polytetrafluoroethylene sintered block.

8. The method according to claim 7, characterized in that The cold pressing conditions include: The pressure is 25-35 MPa; and / or the holding time is 0.5-2 min.

9. The method according to claim 7, characterized in that: The sintering comprises: The cold pressed product is heated to 150-250°C at a heating rate of 2-6°C / min and kept at that temperature for 1-3h, and then heated to 360-380°C at a heating rate of 2-6°C / min and kept at that temperature for 1-3h.

10. Cross-linked polytetrafluoroethylene prepared by the method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Method for preparing cross-linked polytetrafluoroethylene through electron beam irradiation

    CN101824158A

  • Product having reduced friction and improved abrasion resistance

    CN1164541A

  • Method for manufacturing cross-linked fluororesin composite material

    JP2010155443A

  • Production method of polytetrafluoroethylene molded product, production method of polytetrafluoroethylene film, and production method of laminate

    JP2022152516A

  • Method of the radiation-chemical modification of the polytetrafluorehylene and the substance produced on its basis

    RU2304592C1